A cross-sectional study of psychosocial variables associated with medication burden among type 2 diabetes mellitus with multiple comorbidities in geriatric patients - Williams, Helen; Ranganathan, Srinivasan (Rzeszów University Press, 2025)
Introduction and aim. As the population ages, the management of type 2 diabetes mellitus in older adults with multiple comorbidities becomes more complex. Geriatric patients often face a medication burden, impacting their quality of life and adherence. Psychosocial variables such as depression, anxiety, social support, and health literacy may influence how patients cope with their medications. This study explores the relationship between these variables and the burden in geriatric patients with type 2 diabetes and comorbidities, offering insight into improving care and outcomes. Material and methods. The cross-sectional survey was carried out from April to September 2024. 250 patients were included. The demographics of the participants, the burden of the disease, polypharmacy, the burden of the medication, and the psychosocial variables were evaluated. Univariate and multivariate linear regression analyzes assessed the variables associated with the burden of medications. Results. There was a positive correlation between the belief in medication, depression, disease burden, number of medications, number of comorbidities, and medication burden (p<0.05). Knowledge about medications was not significantly correlated with the burden (p>0.05). Conclusion. Low self-efficacy, depression, polypharmacy, high disease burden, and decreased medication satisfaction can all contribute to medication burden. Comprehending these factors helps identify patients with geriatric diabetes and enables personalized treatment to ease their burden.
This work was approved by the Institutional Review Board of Bhaarath Medical College and Hospital. The study was carried out from April to September 2024 (approval number 1056/2024).
Keywords: geriatric patients; medication burden; multiple comorbidities; psychosocial variables; type 2 diabetes mellitus